Determinación de Hepatitis B y VIH en jóvenes de 16 a 25 años con tatuajes, piercing, pirograbados, en el Barrio 24 de Mayo del cantón Santa Rosa. - Zambrano Quezada, Karen R. (2008)
Now a day Young people have increased their preference for decorations of the body like tattoos and piercing, for a variety of reasons world wide. The places and equipment used to perform them, quite often do not present reliable conditions of asepsis, they do not use appropriate procedures of sterilization of materials and personnel who work in these business usually do not have the necessary know ledge about health, sterilization and prevention of contagious diseases.